Semaphorin 3A: A potential target for prevention and treatment of nickel allergy - Liu, Lipei; Watanabe, Megumi; Minami, Norikazu; Yunizar, Mohammad Fadyl; Ichikawa, Tetsuo (Communications biology, 2022)
Metal allergy is one of the typical immune disorders encountered during the application of dental/medical materials and has a highly complex pathogenic mechanism. Semaphorin 3A (Sema3A), a member of the semaphorin family, is reported to be involved in various immune disorders. However, its role in metal allergy has not been clarified yet. Herein, we show that Sema3A expression was upregulated in nickel (Ni) allergy-induced mouse ear tissue and in NiCl 2 -stimulated mouse keratinocytes. Moreover, Sema3A regulated tumor necrosis factor-alpha production and mitogen-activated protein kinase activation in keratinocytes. The specific deletion of Sema3A in keratinocytes did not affect immune cell infiltration but reduced edema and ear swelling; it also impeded Th1 responses to cause a slight alleviation in Ni allergy in mice. Our results demonstrate that Sema3A promotes the development of metal allergy and should be explored as a potential target for the prevention and treatment of metal allergy. Semaphorin 3A is upregulated in keratinocytes upon nickel exposure, subsequently promoting Th1 cytokine responses and driving nickel allergic reactions.